2020
DOI: 10.1002/cctc.202000148
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Copper‐based Silica‐coated Magnetic Nanocatalyst for Efficient One‐pot Synthesis of Chalcones via A3 Coupling of Aldehydes‐Alkynes‐Amines

Abstract: In the present work, we have synthesized bioactive and pharmacologically important chalcone motifs by employing green and efficient silica-coated magnetically separable catalyst, Cu@DBM@ASMNPs. The highly proficient nanocatalyst proves its invincibility for the solvent-free one-pot synthesis of chalcone moieties by A 3 coupling of aldehydes-alkynes-amines in good to excellent yields. The fabricated Cu@DBM@ASMNPs was structurally and chemically analyzed by various techniques such as FT-IR, SEM, TEM, VSM, ICP-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…1a). 40 A broad peak at 3430 cm −1 in all the spectra originated due to the presence of hydroxyl groups. The silica coating over the surface of the MNPs was further corroborated by the presence of a band near 1092 cm −1 which corresponds to the Si-O stretching vibration (Fig.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…1a). 40 A broad peak at 3430 cm −1 in all the spectra originated due to the presence of hydroxyl groups. The silica coating over the surface of the MNPs was further corroborated by the presence of a band near 1092 cm −1 which corresponds to the Si-O stretching vibration (Fig.…”
Section: Introductionmentioning
confidence: 95%
“…24,25 In this context, the interest of researchers is continually focused on the design and development of readily recoverable, reusable and economically feasible photocatalysts that allow promising prospects of deploying an abundant, renewable and clean source of solar energy or visible light for multifaceted catalytic applications. [24][25][26] In light of our on-going interest in developing heterogeneous photocatalysts and our group's expertise in the field of heterogeneous catalysis, [27][28][29][30][31] we became inspired to develop a viable and efficient noble metal free heterogeneous photo catalytic system that exhibits high stability and easy processability. Subsequentially, we devoted our attention toward harnessing the synergistic effects of facile recoverability of magnetic nanoparticles and photoactive properties of Earth abundant metal-based complexes that can ultimately serve as competent photocatalysts to address the limitations associated with conventional photoredox based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Fe 3 O 4 ; MNPs) including cost-effectiveness, reusability, easy operation, facile synthesis, low toxicity and good magnetic performance, they have been further explored in a variety of disciplines and are commonly used as magnetic extraction materials. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Moreover, a wide variety of functional moieties can be grafted over the surface of magnetic nanocomposites, which make further modifications and reactions more convenient. The introduction of magnetism in COFs has proven to be an effective strategy to solve the recovery problem of COFs.…”
Section: Introductionmentioning
confidence: 99%
“…But, research on PI-COFs as catalytic supports is scarcely reported. Therefore, taking the above-mentioned advantages into account and in continuation of our efforts towards the development of sustainable heterogeneous catalysts, [50][51][52][53][54][55][56] in this study, a PI-COF is rationally fabricated by the condensation of pyromellitic dianhydride (PMDA) and melamine (MA). Furthermore, the Cu(II)coordinated polyimide COF material (Cu@PI-COF) is facilely synthesized under room temperature.…”
Section: Introductionmentioning
confidence: 99%